2021
DOI: 10.9778/cmajo.20200283
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interventions targeting gut microbiota on depressive symptoms: a systematic review and meta-analysis

Abstract: Mounting evidence supports the concept of a microbiota-gut-brain axis and suggests that this axis is perturbed in neuropsychiatric disorders. The gut microbiota regulates host exposure to its products by modulating gut epithelial and blood-brain permeability, 1,2 both of which are altered in patients with major depressive disorder. [3][4][5][6] In addition, patients with major depressive dis order have shown substantial shifts in both the relative abun dance of taxa and the neuroactive metabolic potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 84 publications
0
10
0
1
Order By: Relevance
“…Hofmeister et al [38 ▪▪ ] conducted a meta-analysis of 50 randomized controlled trials that showed that probiotic, prebiotic and synbiotic interventions had a statistically significant benefit, while faecal microbiota transplantation (FMT) and parabiotics (compounds that contain inactivated parts of probiotics) did not. Another recent meta-analysis published in 2022 by Sequeira et al [39 ▪▪ ] pointed out that, while probiotics overall did not seem to affect mood on a qualitative level, quantitative measures of depression and psychiatric distress improved slightly in individuals taking probiotics.…”
Section: Psychobiotics In the Treatment Of Mood Disordersmentioning
confidence: 99%
“…Hofmeister et al [38 ▪▪ ] conducted a meta-analysis of 50 randomized controlled trials that showed that probiotic, prebiotic and synbiotic interventions had a statistically significant benefit, while faecal microbiota transplantation (FMT) and parabiotics (compounds that contain inactivated parts of probiotics) did not. Another recent meta-analysis published in 2022 by Sequeira et al [39 ▪▪ ] pointed out that, while probiotics overall did not seem to affect mood on a qualitative level, quantitative measures of depression and psychiatric distress improved slightly in individuals taking probiotics.…”
Section: Psychobiotics In the Treatment Of Mood Disordersmentioning
confidence: 99%
“…Administration of the 4-week multispecies probiotics intervention ( Bifidobacterium bifidum W23, Bifidobacterium lactis W52, Lactobacillus acidophilus W37, Lactobacillus brevis W63, Lactobacillus casei W56, Lactobacillus salivarius W24, and Lactococcus lactis W19 and W58) resulted in a significant reduction in overall cognitive reactivity to sad mood, which was largely accounted for by reduced rumination and aggressive thoughts [ 91 ]. To confirm the hypothesis that probiotics administration is associated with a significant reduction in depression, several systematic reviews and meta-analyses of the existing evidence were conducted [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. The evidence for probiotics alleviating depressive symptoms is compelling, which is confirmed by the secondary evidence found, but additional double-blind randomized control trials in clinical populations are necessitated to further assess efficacy.…”
Section: Can Psychobiotics Minimize the Mental Health Disorders Conne...mentioning
confidence: 99%
“…Весьма впечатляют результаты метаанализа 50 ран домизированных контролируемых исследований, по священных влиянию вмешательств, направленных на микробиом (а именно применение пробиотиков, пребио тиков, синбиотиков или трансплантации фекальной ми кробиоты) на симптомы депрессии у пациентов в воз расте 18 лет и старше [125]. Применение пробиотиков, пребиотиков и синбиотиков при депрессивных симпто мах продемонстрировало статистически значимые улуч шения депрессии, в то время как ни в одном из еди ничных исследований по трансплантации фекальной микробиоты не было показано пользы [125].…”
Section: поведение когнитивные функции и эмоцииunclassified